Avaliação na aula de música? Um estudo com professores de música da Rede de Ensino Municipal de São Carlos/SP - Rodrigues, Flavia Baldacini Navarro (2021)
This is an exploratory study which sought to investigate the assessment of student learning process in Music classes at the Municipal Education Network of São Carlos/SP. The specific objectives of this work are: to verify how the formation and professional performance of teachers takes place as well as to know the planning and types of assessment that these teachers know and practice; analyze the evaluation criteria used to assess students' musical learning and identify which musical content is being evaluated. The theoretical framework used to analyze data was formed from the ideas of four authors: Haydt (2008), Hoffmann (2009), Luckesi (2011a; 2011b) and Zabala (1998) who deal with: the concept of evaluation, types of assessment, assessment instruments, assessment results and its benefits for the daily lives of teachers and students. In order to deal specifically with the assessment in Music class, we used the ideas of the author Swanwick (2003; 2014), who discusses criteria and suggestions for assessing musical learning. The online questionnaire was used as an instrument for data collection and, for data processing, the content analysis was organized into categories based on the specific objectives of this work. The questionnaire was sent by e-mail to all eleven teachers who work in the municipality teaching music classes, with responses from seven of them (response rate of 63.6%). The analysis of the answers shows that the teachers are young, most of them have a degree in Music, and they also declare to feel some kind of difficulty in evaluating their students. In addition, the assessments most used by them are diagnostic and formative, and the most voted assessment tool was observation. Other data from the analysis framed the teachers' evaluation criteria in the dimensions of Materials and Swanwick's Expression (2014). Finally, the content that teachers assess is of an attitudinal, conceptual and procedural nature, according to Zabala (1998), with a prevalence of the attitudinal nature. In the final considerations, two suggestions for assessment that can be used in large classes are presented: the minute paper (MENEZES, 2010) and compositions in small groups.